Study of Medicinal Plants in the Geothermal Area of Mount Seulawah Agam, Aceh Besar District, Indonesia - MUHAMMAD DOUDI; SAIDA RASNOVI; DAHLAN DAHLAN; HENDRIX INDRA KUSUMA; MUSLICH HIDAYAT (Jurnal Natural, 2021)
The area of mount Seulawah Agam is an area of active volcano paths that impact the appearance of volcanic symptoms, that will affect the species of plants that grow in the area. This study aims to determine the potential of medicinal plant species and their diversity in the geothermal area of Seulawah Agam, Aceh Besar district. The data collection was carried out using multiple square plots placed using stratified sampling based on the soil temperature zone at a predetermined. Each area is set on four impartial actions in systematic random. The name of the species and its individual quantity of each potential plant was documented and analyzed accordingly. Then, they were analyzed based on scientific journals and identification books for medicinal plants. Data analysis was performed using importance value index and Diversity Index. The study found there were 32 species of 21 families of medicinal plants were identified started from the growth rates of seedlings, saplings, poles, and trees. The medicinal plants' diversity index analysis at each growth rate is classified into the medium category. Based on literature studies, plants' parts are commonly used as medicines such as leaves roots, sap, bark, and flowers. Utilization can be used to treat a variety of diseases and illnesses, as well as a parasitic infection. The result shows that the geothermal area of Seulawah Agam in Aceh Besar district has excellent resources and potential for medicinal plants that become used for the benefit of the surrounding community: they need to be maintained so that they still be beneficial for future generations.